Differentiation of Ganglioside Isomers by MALDI Tandem Mass Spectrometry with Alkali Earth Metal Additives. (10th August 2015) - Park, Woojin; Lee, Dongkun; Cha, Sangwon
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10441-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>